The influence of compression garments on recovery during a triathlon training camp: a pilot study - Leabeater, A.; James, L.; Driller, M. (Journal of Science and Cycling, 2022)
Triathletes often schedule intense training camps into their program to promote functional overreaching, although these periods pose a greater risk of illness or injury due to heightened training load. To mitigate this risk, triathletes may implement recovery strategies such as the use of compression garments. However, little is known about the influence of such garments during multi-day exercise periods. Ten highly-trained triathletes (6 male, 4 female, mean ± SD age; 32 ± 8 y) completed a six-day intensive training block and were randomly assigned to one of two recovery groups; donning lower body compression tights (COMP, n = 5) for at least 6 hours following the last training session each day, or no compression (CON, n = 5). Physical performance data (6s sprint, 30s sprint, 4-minute mean power cycling tests) was collected on Day 1 and Day 6 of the training camp and subjective wellbeing monitoring was completed daily. There were no significant group x time interactions for any of the performance or perceptual measures (p > 0.05). However, a large (d = -1.35) reduction in perceived stress was observed from Day 1 to Day 5 in COMP compared to CON; and perceived muscle soreness was associated with significant main effects for group (p = 0.047) and time (p = 0.02), with COMP lower than CON on Day 4 and Day 6. Lower-body compression garments may reduce perceived stress and muscle soreness during an intense six-day triathlon training camp, with minimal influence on physical performance.